Protocol for a scoping review of traditional medicine research methods, methodologies, frameworks and strategies - Ijaz, Nadine; Hunter, Jennifer; Grant, Suzanne; Templeman, Kate (Frontiers in Medicine, 2024)
Background The World Health Organization (WHO) has called for the evidence-informed integration of traditional medicine (TM) into health systems. Research rigor requires a good “fit” between research designs and what is being studied. The expectation that TM research fully adheres to biomedical evidentiary norms potentially creates tensions, as TM paradigms have their own distinct features. A scoping review will be conducted to describe and characterize the research approaches used in TM and their paradigmatic alignment with the TM being studied. Methods This scoping review protocol was informed by Joanna Briggs Institute (JBI) methods. This protocol outlines an a priori conceptual framework, provisionally termed “paradigmatic alignment.” The review will include all populations, TM types, research approaches (i.e., methods, methodologies, frameworks, strategies), cultural contexts, and health care settings. Up to 38 English and non-English language databases will be searched sequentially for both published and gray literature until reaching data saturation across relevant concepts and contexts. Analysis will begin deductively, using a pre-piloted data extraction template to describe the TM research approaches. A basic qualitative content analysis of a sample of evidence sources will explore how research approaches are applied or modified to align with the TM therapeutic paradigm, and the manner in which they co-exist, contrast, complement or align with established biomedical research approaches. The findings will be narrated and summarized in charting tables and figures. The review will be reported according to the PRISMA scoping review extension. Consultative engagement with knowledge users across all review stages is planned. Discussion Aligned with the principle of Two-Eyed Seeing (Etuaptmumk), wherein Indigenous/traditional and biomedical knowledges may equitably co-exist, this review promises to advance scholarly insights of critical value in an increasingly pluralistic, globalized world. Clinical trial registration: https://clinicaltrials.gov/, identifier INPLASY2023110071.